Factors Affecting Non-Performing Loans of Conventional Banking in Indonesia Stock Exchange - Hanna Khoirunisa; Reniati Karnasi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
This study aims to analyze the factors influencing credit risk in banks. The sample used was 36 conventional banks listed on the Indonesia Stock Exchange for the 2017-2021 period. The sampling technique used is purposive sampling and the analysis method used is panel data regression. The independent variables in this study consist of lending interest rates, return on assets, liquidity ratio, capital adequacy ratio, cost income ratio, inflation rate, and gross domestic product while the dependent variables are non-performing loans. The results showed that the rate of return on assets, capital adequacy ratio, and gross domestic product had a significant negative effect on the level of non-performing loans and the inflation rate had a significant positive effect on the level of non-performing loans. Lending interest rates and liquidity ratios have no effect on the level of non-performing loans. The findings of this study are expected to be a reference for conventional banks in minimizing credit risk by increasing their profitability and developing better credit management when economic growth and inflation rates are getting higher.